Reconstructing ‘Irfānī Epistemology: Najm al-Dīn Kubrā and the Philosophical Legitimacy of Mystical Knowledge - Arrazy Hasyim; Putra Aldomi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2026)
Contemporary discussions on Islamic epistemology continue to privilege rational and empirical modes of knowledge, while the epistemological legitimacy of mystical intuition remains contested. Existing studies on Najm al-Dīn Kubrā have largely focused on his contributions to Sufism, Qur'anic exegesis, and the Kubrawīyah order, with limited attention given to the philosophical structure of his ‘irfānī epistemology. This study aims to reconstruct Kubrā's epistemological framework and examine how spiritual intuition functions as a legitimate source of knowledge within the Islamic intellectual tradition. Employing qualitative library research with a phenomenological approach inspired by William James, the study analyses Kubrā's principal works, Fawā’iḥ al-Jamāl wa-Fawātīḥ al-Jalāl and al-Ta’wīlāt al-Najmīyah, in dialogue with the epistemological formulations of al-Ḥakīm al-Tirmidhī, al-Ghazālī, and Ibn Sīnā. The findings demonstrate that Kubrā developed a coherent ‘irfānī epistemology in which kashf, dhawq, and mushāhadah constitute valid epistemic modes that complement empirical observation and rational inquiry through spiritual discipline (mujāhadah). Furthermore, the concepts of Shaykh al-Ghayb, Kitāb al-Ghayb, and Ism al-Ghayb represent Kubrā's original contribution to explaining the process of mystical cognition. This reconstruction offers an alternative perspective to al-Jābirī's critique by showing that ‘irfānī epistemology should be understood not as an obstacle to intellectual development but as an expansion of the epistemological horizon within the Islamic intellectual tradition. The study contributes to contemporary discussions on Islamic epistemology, philosophy of religion, and Sufi hermeneutics by demonstrating that mystical knowledge constitutes a systematic theory of knowledge rather than merely a form of personal religious experience.